RUCULA GROWING IN A HYDROPONIC SYSTEM UNDER DIFFERENT SALT CONCENTRATIONS - Guardabaxo, C. M.S.; Assis, K. C.C. [UNESP]; Figueiredo, F. C.; Silva, L. F. [UNESP] (My University, 2020)
The aim of this study was to evaluate different concentrations of salts in the nutrient solution proposed by Furlani (1999) in hydroponic arugula cultivation in the deep film techinique (DFT) system in a protected environment. The design used was completely randomized (DIC) with four replications, with the treatments being five concentrations of salts: 33%, 67%, 100%, 133% and 167% in relation to the original concentration with adaptation of the nutrient copper in the concentration 0.064 mg L-1. The seedlings were conducted for 30 days in a hydroponic system (DFT). The results showed that the increase of salts from the 67% dose did not show significant gains in dry mass. The results also did not show significant results in leaf contents, which in high concentrations showed a negative interaction between some nutrients. For the accumulation of nutrients nitrogen, phosphorus and potassium and chemical composition, no concentration of salts above 100% provided an effective increase that justified the increase in the cost inherent to the increase in salts in the solution. Arugula cultivation shows better development with salt concentrations between 67 and 100%.
CULTIVO DA RÚCULA EM SISTEMA HIDROPÔNICO SOB DIFERENTES CONCENTRAÇÕES DE SAIS
Keywords: Brassica; Eruca sativa; Floating; Nutritional yield; Nutritive Solution